BIOFILM PRODUCTION AND MULTIDRUG RESISTANT AMONG THE ISOLATES FROM ACUTE AND CHRONIC WOUND INFECTIONS - S.TAMARAISELVI; S.R.SWARNA; RADHA MADHAVAN; S.GOMATHI (International Journal of Pharma and Bio Sciences, 2015)
Chronic wounds are major burden for the healthcare system due to the delayed wound healing. One important factor associated with the delayed wound healing is the bacterial biofilms that are polymicrobial and are mostly resistant to antibiotics. The present study was done to demonstrate the biofilm formation of the isolates from chronic and acute wound infection and its relation with multi-drug resistance. Pus swabs were collected from 34 patients with acute wound infection and 44 patients with chronic wound infection. Isolation and identification of the specimen was done using standard procedure followed by screening of drug resistance by antibiotic susceptibility testing. Biofilm formation was detected using microtitre plate method. 98.33% (59/60) of the isolates from chronic wound infection were biofilm producer as compared to 72.5% (29/40) isolates from acute wound infection. Significant difference was noted for the isolates from chronic wound infection in association with multi-drug resistance and biofilm formation.